ANALYSIS THE ABILITY UNDERSTANDING THE CONCEPT STUDENTS IN CLASS VIII OF SMP ORAHILI FONDRAKO QUADRATIC - Ronal Raigen Giawa (Afore : Jurnal Pendidikan Matematika, 2023)
One of the problem which obtained by the researcher was the lack of ability in understanding mathematical concepts at the VIII grade students at orahili fondako on quadratic equation material. This research is aimed to describe the ability of mathematical concept understanding of students at the VIII grade at orahili fondako village on quadratic equation material and to know what are the students' difficulty at the VIII grade of orahili fondako village in finishing the concept comprehending ability especially on quadratic equation material. This research used qualitative descriptive research. The subject of the research was students at VIII grade in orahili fondako village which consists of 15 persons. The technique of collecting data was done by observation and test to the subject of the research. Data was analyzed by the steps as follow, data reduction, data display and verifing conclusion. As the result of the research shows that the mathematical concepts understanding at the VIII grade on quadratic equation material takes place under category by the percentage was 33%. The difficulties which got by the students in finising a test of mathematical concept understanding ability on quadratic equation material which students was lack to comprehend the test of the test given where, the students did not know what is the meaning and the purpose was asked of the case, then the students also still lack to elaborate that concept in a test, so the students were not able to answer the case of the test given and the students still lacked in understanding the steps in describing quadratic equation graphic. Furthermore, students still not able to apply the concept of quadratic equation in the case of problem solving. The researcher suggesting that the teacher and parent be collaborated on online learning proces which is applying nowdays so that the students' mathematical concept understanding be improved.